Transportes em Copas do Mundo FIFA : um procedimento para o cálculo e a minimização da pegada de carbono - Pereira, Rodrigo Pinheiro Tóffano (2018)
The environmental impact of transportation in mega-events is relevant, especially when it comes to the World Cup of the International Football Federation (FIFA), the biggest celebration in the world for a single sport. The 2014 FIFA World Cup BrazilTM was the first event ever to have its full carbon footprint calculated and reported by its respective organisation. Therefore, the objective of this work is to propose and apply a procedure capable of measuring the carbon footprint of the transportation and accommodation of the participants of a FIFA World CupTM event. Bibliographical research was carried out, as well as data collection from the 2014 FIFA World Cup BrazilTM for purposes of applying the proposed procedure. The results obtained allowed comparative analyses and the verification of trends in favor of proposing general measures of minimisation for future events. The proposed procedure was effective and constitutes an alternative to the methodology used by FIFA. However, the total standards found are almost 2.15 times lower than the official ones published, as much data used by FIFA is based on global averages and not specific to the reality of the host country. Thus, the results show the importance of using local data to obtain accurate greenhouse gas (GHG) emissions from sporting events; and consequently, the importance of correctly planning the means of transportation used by the general public during the competition.